Development and validation of RP-HPLC method for stability evaluation of model hydrazone, containing a pyrrole ring - Diana Tzankova; Lily Peikova; Stanislava Vladimirova; Maya Georgieva (Pensoft Publishers, 2019)
RP-HPLC method with UV detection was developed and validated for determination of the chemical stability and stability in close to physiological conditions of a model pyrrole hydrazone ethyl 5-(4-bromophenyl)-1-(1-(2-(4-hydroxy-3-methoxybenzylidene) hydrazineyl)-4-methyl-1-oxopentan-2-yl)-2-methyl-1H-pyrrole-3-carboxylate (D_5d), containing susceptible to hydrolysis hydrazone group. The evaluated substance was subjected to the influence of a variety of pH , representing the main physiological values of 37°C and corresponding pH values in the stomach (pH 2.0), blood (pH 7.4) and small intestine (pH 9.0). Chemical stability in a highly alkaline medium with a pH of 13.0 was also evaluated. The hydrazone I tested was found to be stable at pH 7.4 and pH 9.0 and 37 ° C and hydrolyzed under strong acidic (pH 2.0) and highly alkaline media (pH 13.0) and at the same temperature.The products of hydrolysis were identified to be the initial hydrazide and aldehyde, pointing the hydrazone group as most liable.